Grammar, discourse, context: grammar and usage in language variation and change - Bech, Kristin; Möhlig-Falke, Ruth (Diskursmuster, 2020)
Frontmatter -- Contents -- List of tables and figures -- Grammar – discourse – context: Grammatical variation and change and the usage-based perspective / Möhlig-Falke, Ruth / Bech, Kristin -- Contextualizing Old English noun phrases / Bech, Kristin -- Syntax, text type, genre and authorial voice in Old English: A data-driven approach / Los, Bettelou / Lubbers, Thijs -- The intensifier system of the Ormulum and the interplay of micro-level and macro-level contexts in linguistic change / Méndez-Naya, Belén -- Constructional change across the lifespan: The nominative and infinitive in early modern writers / Anthonissen, Lynn -- Contextualizing dual-form adverbs in the Old Bailey Corpus: An assessment of semantic, pragmatic, and sociolinguistic factors / Möhlig-Falke, Ruth -- Bridging contexts in the reanalysis of naturally as a sentence adverb: A corpus study / Haumann, Dagmar / Killie, Kristin -- From parataxis to amalgamation: The emergence of the sentence-final is all construction in the history of American English / Shibasaki, Reijirou -- The role of context in the entrenchment of new grammatical markers in World Englishes / Seoane, Elena -- Paradigms, host classes, and ancillariness: A comparison of three approaches to grammatical status / Konvička, Martin -- The motivated unmotivated: Variation, function and context / De Smet, Hendrik -- Grammar in context: On the role of hypercharacterization in language variation and change / López-Couso, María José -- List of contributors -- Index
restricted access online access with authorization star
Keywords: Aufsatzsammlung; Sprachwandel; Sprachvariante; Sprachgebrauch; Grammatik; Englisch